Description of a new Phytocoris (Compsocerocoris) species (Heteroptera: Miridae) from southeastern Anatolia with a checklist of the Phytocoris species of Turkey - cerci, Baris; Ozgen, Inanc; Tezcan, Serdar (Taylor & Francis Ltd, 2021)
A new species of the genus Phytocoris Fallen, subgenus Compsocerocoris, is described from southeastern Anatolia, Turkey: Phytocoris iyribozi sp. n. The new species is closely related to the species of the dashtanus species-group within the subgenus but differs from them by remarkably small size, short first antennal segment, small ocular index of male and shape of left paramere. To distinguish the new species, an updated identification key of the dashtanus species-group is presented. Additionally, a checklist of Phytocoris species of Turkey with chorotypes of each species is given. A total of 43 species of Phytocoris is listed from Turkey and the chorotype analysis revealed that 23.3% (10 of 43) of species are endemic to Turkey and 60.6% (26 of 43) are distributed only locally in Turkey and its neighbouring countries.
Keywords: dashtanus species group; checklist; chorotype analysis; identification key